2009
DOI: 10.1177/1352458509354552
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrics and normative data for the Multiple Sclerosis Functional Composite: replacing the PASAT with the Symbol Digit Modalities Test

Abstract: The MS Functional Composite (MSFC) is a continuous scale of neurological disability for patients with multiple sclerosis (MS). Cognition is represented by the Paced Auditory Serial Addition Test (PASAT), although the Symbol Digit Modalities Test (SDMT) has been proposed as a promising alternative. MSFC scores were calculated using either the PASAT or the SDMT with the following reference populations: National Multiple Sclerosis Society (NMSS) Task Force, 400 MS patients, and 100 normal controls. A subgroup of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
175
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(189 citation statements)
references
References 49 publications
9
175
0
2
Order By: Relevance
“…Recent studies have suggested replacing the Paced Auditory Serial Addition Test in the MSFC with the Symbol Digit Modalities Test, and the results of the present study are consistent with this suggestion. 42,43 A potential limitation of this study is the small sample size (N = 53), a factor that may limit the ability to detect small effect sizes. In addition, this study sample was predominantly women (85%), and, thus, its findings may not generalize to men.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested replacing the Paced Auditory Serial Addition Test in the MSFC with the Symbol Digit Modalities Test, and the results of the present study are consistent with this suggestion. 42,43 A potential limitation of this study is the small sample size (N = 53), a factor that may limit the ability to detect small effect sizes. In addition, this study sample was predominantly women (85%), and, thus, its findings may not generalize to men.…”
Section: Discussionmentioning
confidence: 99%
“…A study in a large group of patients with MS and controls demonstrated the validity of both the PASAT and SDMT version of the MSFC, with slightly better ability of the SDMT version in predicting diagnosis, disease course, and work disability. 9 The SDMT is also among the more reliable and sensitive 10 tests in the MS literature and is a robust correlate of several brain imaging findings.…”
mentioning
confidence: 99%
“…Patients have an aversive feeling towards PASAT 12 , unaware that bad scores may not reflect neurological impairment 11 . Recent studies have even suggested that PASAT should be replaced by another test for MSFC assessment 13 .…”
mentioning
confidence: 99%